An Evaluation of the Financial Sustainability of Remote Australian Local Councils*. Issue 2 (25th March 2022) - Fellows, Caillan; Dollery, Brian; Marques, Rui
Abstract : Spatial remoteness in the sense of great distances between population centres and limited access to public services is an on‐going problem in Australian local government, where there exist large, sparsely populated regions dominated by the 'tyranny of distance'. From a public policy perspective, it is important to understand the impact of remoteness on local authorities. Accordingly, in this paper, we estimate the relationship between remoteness and financial sustainability using a 2014–2018 sample of Australian local governments. In general, we find only limited empirical evidence for a relationship between geographical remoteness and financial sustainability as we have proxied it.